tim x: 32.35 :3x=81
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2^x.2^2.2^2=2^3\Rightarrow2^{x+2+2}=2^3\Rightarrow x+4=3\Rightarrow x=-1\)-1
\(\left(5^2+3^2\right).x+\left(5^2-3^2\right).x-40.x=10^2\)
\(\Rightarrow x.\left(5^2+3^2+5^2-3^2-40\right)=10^2\)
\(\Rightarrow x.\left(2.5^2-40\right)=10^2\)
\(\Rightarrow x.10=10^2\Rightarrow x=10^2:10\Rightarrow x=10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
<=> 48x^2 - 12x - 20x + 5 + 3x - 48x^2 - 7 + 112x = 81
<=> -32x + 115x = 81 + 2
<=> 83x = 83
<=> x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 4x(x - 5) - (x - 1)(4x - 3) = 5
4x2 - 20x - (4x2 - 3x - 4x + 3) = 5
4x2 - 20x - 4x2 + 3x + 4x - 3 = 5
-13x - 3 = 5
\(\Rightarrow\) -13x = 8
\(\Rightarrow\) x = \(\dfrac{-8}{13}\)
b) (3x - 4)(x - 2) = 3x(x - 9) - 3
3x2 - 6x - 4x + 8 = 3x2 - 27x - 3
3x2 - 10x + 8 - 3x2 + 27x + 3 = 0
17x + 11 = 0
\(\Rightarrow\) 17x = -11
\(\Rightarrow\) x = \(\dfrac{-11}{17}\)
c) x2 - 81 = 0
\(\Rightarrow\) x2 = 81
\(\Rightarrow\) x = \(\pm\) 9
d) 3x2 - 75 = 0
3(x2 - 25) = 0
\(\Rightarrow\) x2 - 25 = 0
\(\Rightarrow\) x2 = 25
\(\Rightarrow\) x = \(\pm\)5
e) x2 - 4x + 3 = 0
x2 - x - 3x + 3 = 0
(x2 - x) - (3x - 3) = 0
x(x - 1) - 3(x - 1) = 0
(x - 3)(x - 1) = 0
\(\Leftrightarrow\left\{{}\begin{matrix}x-3=0\\x-1=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=3\\x=1\end{matrix}\right.\)
xin lỗi vì chữa đề
![](https://rs.olm.vn/images/avt/0.png?1311)
Đặt \(A=\frac{3}{5.8}+\frac{3}{8.11}+\frac{3}{11.14}+...+\frac{3}{32.35}\)
\(A=\frac{1}{5}-\frac{1}{8}+\frac{1}{8}-\frac{1}{11}+\frac{1}{11}-\frac{1}{14}+...+\frac{1}{32}-\frac{1}{35}\)
\(A=\frac{1}{5}-\frac{1}{35}=\frac{6}{35}\)
\(\Rightarrow x+\frac{6}{35}=-\frac{2}{7}\Rightarrow x=-\frac{2}{7}-\frac{6}{35}=-\frac{16}{35}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
<=> 48x^2 - 12x - 20x + 5 + 3x - 48x^2 - 7 + 112x = 81
<=> -32x + 115x = 81 + 2
<=> 83x = 83
=>x = 1
hc tốt
(12x - 5)* (4x - 1) + ( 3x - 7) * ( 1 - 16x ) = 81
<=> 48x^2 - 12x - 20x + 5 + 3x - 48x^2 - 7 + 112x = 81
<=> -32x + 115x = 81 + 2
<=> 83x = 83
<=> x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(8\sqrt{x}-3\sqrt{\frac{4}{81}}=5,2\)
\(\Rightarrow8\sqrt{x}-3.\frac{2}{9}=5,2\)
\(\Rightarrow8\sqrt{x}-\frac{2}{3}=5,2\)
\(\Rightarrow8\sqrt{x}=5,2+\frac{2}{3}\)
\(\Rightarrow8\sqrt{x}=\frac{40}{3}\)
\(\Rightarrow\sqrt{x}=\frac{40}{3}:8\)
\(\Rightarrow\sqrt{x}=\frac{5}{3}\)
\(\Rightarrow x=\frac{25}{9}\)
b)\(12-3x^2=10+\sqrt{\frac{25}{16}}\)
\(\Rightarrow12-3x^2=10+\frac{5}{4}\)
\(\Rightarrow12-3x^2=11,25\)
\(\Rightarrow3x^2=12-11,25\)
\(\Rightarrow3x^2=0,75\)
\(\Rightarrow x^2=0,25\)
\(\Rightarrow x=\sqrt{0,25}\)
\(\Rightarrow x=0,5\)